The effect of peppermint oil addition on the physical stability, irritability, and penetration of nanostructured lipid carrier coenzyme Q10 - Tristiana Erawati; Rizki A. Arifiani; Andang Miatmoko; Dewi M. Hariyadi; Noorma Rosita; Tutiek Purwanti (Journal of Public Health in Africa, 2023)
Background: Coenzyme Q10 is formulated into Nanostructured Lipid Carrier (NLC) added with peppermint oil (PO) 0% (F1), 1% (F2), 1.5% (F3) and 2% (F4) to increase its penetration. Objective: This study aims to determine the effect of PO addition on the irritability, stability, and penetration of Coenzyme Q10 in the NLC. Methods: Coenzyme Q10 NLC was prepared using the High Shear Homogenization method. Furthermore, physical characterization was carried out. Physical stability testing was carried out for 90 days at a temperature of 25±5oC and an RH of 60±10%. The in vivo irritation test was observed for mice’s back skin after 24 hours while the penetration study was further evaluated at 2 hours of the sample application. Results: Increasing the PO amount into Coenzyme Q10 NLC reduced the viscosity which was 329.1±15.5 cps for PO 0% to 219.9±2.9 cps for 2% addition. The observation of particle morphology showed that all NLC Coenzyme Q10 has a spherical particle shape with particle size between 188.25±13.22 to 197.80±14.19 nm. All formulas had high entrapment efficiency (80%). PO addition did not cause changes in physical characteristics during 90 days of storage. The 24 hours’ irritation test showed that F2 and F3 are non-irritating. By PO addition skin penetration improved at 2 hours’ penetration study. Conclusion: PO addition up to 2% reduced viscosity, but did not affect particle size and morphology of Coenzyme Q10 NLC. Addition of PO up to 1.5% increased entrapment efficiency, did not irritate and increased the penetration of Coenzyme Q10 NLC.